2021
DOI: 10.3892/ijo.2021.5175
|View full text |Cite|
|
Sign up to set email alerts
|

Emerging roles of non‑coding RNAs in the response of rectal cancer to radiotherapy (Review)

Abstract: Radiotherapy (RT) followed by radical surgery is an effective standard treatment strategy for various types of cancer, including rectal cancer. The response to RT varies among patients, and the radiosensitivity of cancer cells determines the clinical outcome of patients. However, the application of RT to patients with radioresistant tumors may result in radiation-induced toxicity without clinical benefits. Currently, there are no effective methods to predict the response to RT. The limitations of the methods c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 128 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…100,101 Studies have revealed that the dysregulation of lncRNAs is associated with carcinogenesis and CRT resistance. 102 circRNAs are endogenous ncRNAs lacking 5′- and 3′-untranslated regions (UTRs) which are produced by backsplicing of precursor mRNAs. 103 They have a circular structure, evolve conservatively, and are highly stabilized, thereby showing inherent resistance to RNase but can exhibit abnormal expression when they are mediated in cancer progression.…”
Section: Ncrt Resistance/sensitivity-related Cernasmentioning
confidence: 99%
“…100,101 Studies have revealed that the dysregulation of lncRNAs is associated with carcinogenesis and CRT resistance. 102 circRNAs are endogenous ncRNAs lacking 5′- and 3′-untranslated regions (UTRs) which are produced by backsplicing of precursor mRNAs. 103 They have a circular structure, evolve conservatively, and are highly stabilized, thereby showing inherent resistance to RNase but can exhibit abnormal expression when they are mediated in cancer progression.…”
Section: Ncrt Resistance/sensitivity-related Cernasmentioning
confidence: 99%
“…ncRNAs have been widely investigated as diagnostic biomarkers or therapeutic efficacy predictors in cancer ( Li et al, 2020a ; Ha Thi et al, 2021 ; Konoshenko et al, 2021 ). Accurate prediction of response to RT by ncRNAs profiles would undoubtedly improve the prognosis of LAGC patients and allow individualized treatment.…”
Section: Introductionmentioning
confidence: 99%